Identification of Women's Quality of Life Home Business Actors with Influencing Factors - Thathit Manon Andini; Dini Kurniawati; Aini Alifatin; Nur Hayatin (Universitas Muhammadiyah Malang, 2022)
The basic problem in women's empowerment that has occurred so far is the low participation of women in development. In addition, there are still various forms of discriminatory practices against women. In the social context, there are still gaps in the roles of men and women (Education, Health and public participation involvement). Susenas data (National Socio-Economic Survey) 2003 shows that the education level of Indonesian women is still low. If there are physical, mental, or social health problems, it can reduce the value of quality of life. When women are busy in fulfilling the family's economy, will their physical, mental and social conditions become healthy? Will their quality of life be maintained when they become the foundation of the family's economy? What are their quality of life indicators? This study aims to determine their quality of life associated with various factors (Health, education, economy, etc.). In this study, the researcher chose to use qualitative methods or descriptive analysis to identify and describe the quality of life of women entrepreneurs at home and the factors that influence them. From the results of the study, it can be seen from the personal data, The women who do home-based businesses are still of productive age, with minimal high school education. Their efforts can generate sufficient income to meet their needs. It can be concluded that the quality of life of the women is good, as well as mental conditions (self-satisfaction, self-motivation). The dominant factors in influencing mothers to run their businesses are educational factors, self-confidence in running their business, self-satisfaction and also feeling healthy, feeling safe.